Getting thin films by SIC PECVD - Omarov, M.A.; Prikhodko, O.Yu.; Klimenov, V.V.; Aitmukan, T.; Alpysbayeva, B.E.; Nevmerzhitsky, I.S. (Recent Contributions to Physics, 2012)
In this research work presents the results of obtaining silicon carbide in plasma-enhanced chemical vapor deposition with the application of a magnetic field. Obtained thin films of silicon carbide and cubic silicon carbide differ in their structure and some properties of a semiconductor.